ALISS - A democratic, crowd-sourced, digital resource for community health and wellbeing assets, accessible to all, across Scotland...22nd International Conference on Integrated Care, May 23-25, 2022, Odense, Denmark. - Mackie, Chris (International Journal of Integrated Care (IJIC))
Introduction: ALISS, A Local Information System for Scotland, has the vision that everyone in Scotland can access the information they need to help them live well. ALISS uses open source, open data and open referral principles to provide a digital platform for searching and sharing information about health and wellbeing services, activities, groups, and resources which are openly accessible. Information is 'crowd-sourced' from citizens who operate these services, and from 'editors' trained by the ALISS team. These principles align ALISS with and to people, communities and the third sector across Scotland in support of health and wellbeing. Aims, Objectives, Theory or Methods: ALISS has the following aims: * To increase the availability and accessibility of information about services, groups, activities, and resources that can impact on the health and wellbeing of the people of Scotland, particularly those living with long term conditions, disabled people, unpaid carers and people facing disadvantage. * To support people, communities, professionals, and organisations to share information on services, groups, activities and resources that can impact on the health and wellbeing of the people of Scotland. To thereby make a significant contribution to improving the health and wellbeing of the people of Scotland. Highlights or Results or Key Findings: ALISS is hosted by the Health and Social Care Alliance Scotland (the ALLIANCE). The programme has the following key elements: * Community empowerment approach By encouraging people in communities to add, update or claim information about services, ALISS operates a 'ground-up' approach, reflecting the complexity and diversity of each locality. * User research and service design ALISS is a coproduced system. It utilises service design approaches, complimented by a user researcher based within the team. *Local and national engagement Two engagement workers liaise with organisations and communities across Scotland to promote ALISS, and encourage its use through meetings, workshops, training sessions and networks. * Use of open approaches ALISS is an open-source project, meaning that the code is available for other developers to view and reuse in their own projects which may require similar functionality. ALISS data is also available publicly via an API (application program interface) and conforms to open referral standards. Conclusions: ALISS is an example of "what good looks like", both in terms of the approaches it adopts and its outputs. It has a strategy embedding continuous improvement and ensuring that people remain at the centre of the programme. The strategy seeks "more data", "better data", "better experience", "more users". Implications for applicability/transferability, sustainability, and limitations: The digital health and social care landscape is complex and rapidly changes. The approach to ALISS and learning gained through the programme are applicable to other digital health and care projects. These can ensure that projects put health and wellbeing and people at the centre.